An Assessment Model for Cybercrime Investigation Capacity - James, Joshua I. (2013)
Digital technologies are constantly changing, and with it criminals are finding new ways to abuse these technologies. Cybercrime investigators, then, must also keep their skills and knowledge up to date. This work proposes a holistic training development model - specifically focused on cybercrime investigation - that is based on improving investigator capability while also considering the capacity of the investigator or unit. Along with a training development model, a cybercrime investigation capacity assessment framework is given for attempting to measure capacity throughout the education process. First, a training development model is proposed that focuses on the expansion of investigation capability as well as capacity of investigators and units. Next, a capacity assessment model is given to evaluate the effectiveness of the training program. A description of how the proposed model is being applied to the development of training programs for cybercrime investigators in developing countries will then be given, as well as already observed challenges. Finally, concluding remarks as well as proposed future work is discussed.Comment: 1 figure, World Crime Forum 1st Asian Regional Conference - Information Society and Cybercrime: Challenges for Criminology and Criminal Justic